Altered Energy Mobilization Within the Littoral Food Web in New Habitat Created by Climate-Induced Changes in Lake Water Level - Wang, Kang; Zhao, Kangshun; Xiong, Xiong; Zhu, Huan; Ao, Hongyi; Ma, Kaili; Xie, Zhicai; Wu, Chenxi; Wang, Huan; Zhang, Huan; Zhang, Peiyu; Xu, Jun (Frontiers in Ecology and Evolution, 2022)
Littoral zones in oligotrophic lakes play an essential role in supporting animal consumers and in the exchange of matter between the water body and the terrestrial sources, but are easily altered by changes in water level. We studied Qinghai Lake, a deep oligotrophic lake in northwest China, where lake water level has increased rapidly in recent years, altering the character of the littoral zones. We sampled common organisms and used stable carbon and nitrogen isotope analyses to compare how contributions of different sources (allochthonous and autochthonous) to the diets of consumers differed between sand (original habitat, OH) and submerged grassland (new habitat, NH) substrate habitat conditions. Our results showed that allochthonous resources (i.e., terrestrial detritus) constituted the largest diet proportion of consumers in OH due to poor nutrient conditions, while consumers in NH utilized more autochthonous resources (i.e., Cladophora and phytoplankton). We also found that terrestrial nutrient subsidies from soil and decomposed grass led to increased biomasses of Cladophora, phytoplankton, zooplankton and zoobenthos in NH compared to those in OH, accounting for autochthonous replacement of part of the allochthonous resources in NH. Therefore, hydrological conditions may alter the trophic interactions within littoral food webs, contributing to a more complex and interconnected food web. Overall, our results suggest that the littoral food webs of Qinghai Lake are vulnerable to changes in hydrological conditions, which may be enhanced by climate change.